2004
DOI: 10.1182/blood.v104.11.3463.3463
|View full text |Cite
|
Sign up to set email alerts
|

VAD-t (Vincristine, Adriamycin, Dexamethasone and Low-Dose Thalidomide) Is an Effective Initial Therapy with High Response Rates for Patients with Treatment Naïve Multiple Myeloma (MM).

Abstract: Recent understanding of MM biology suggests that MM cells rely on their microenvironment for disease progression and dissemination. MM cell interaction with stromal cells in the bone marrow microenvironment fosters chemotherapy resistance. Targeting the microenvironment with novel biologic agents such as thalidomide (T) has shown encouraging clinical results in patients with previously untreated as well as relapsed/refractory MM. We have previously shown here that VAD plus low dose T (t) is an effective salvag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2005
2005
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…24 In our MPT study, neurologic toxicity did not differ from that observed in other thalidomidecontaining regimens (e.g., thalidomide plus dexamethasone and/or doxorubicin). 4,20,21,23 In conclusion, MPT is an active combination regimen with an excellent response profile in multiple myeloma although a longer follow-up is required to evaluate its efficacy in terms of disease remission duration and OS. Ongoing randomized trials comparing MP versus MPT will illustrate the real role of MPT in newly diagnosed patients with myeloma.…”
Section: Discussionmentioning
confidence: 99%
“…24 In our MPT study, neurologic toxicity did not differ from that observed in other thalidomidecontaining regimens (e.g., thalidomide plus dexamethasone and/or doxorubicin). 4,20,21,23 In conclusion, MPT is an active combination regimen with an excellent response profile in multiple myeloma although a longer follow-up is required to evaluate its efficacy in terms of disease remission duration and OS. Ongoing randomized trials comparing MP versus MPT will illustrate the real role of MPT in newly diagnosed patients with myeloma.…”
Section: Discussionmentioning
confidence: 99%
“…Os autores observaram que no grupo QT a freqüência de trombose venosa profunda foi de 14,18%, enquanto nos grupos QT+T e QT+ T+ varfarina as freqüências de TVP foram de 34,5% e 31,4%, respectivamente. Chanan-Khan et al 19 empregaram o protocolo VAD-talidomida em 16 pacientes com mieloma múltiplo recém-diagnosticado, usando varfarina, na dose de 1-2 mg como profilaxia antitrombótica, observando 12% de trombose venosa profunda. Em 2005, Cavo et al 20 relataram os resultados do estudo expandido iniciado em 2004.…”
Section: Talidomida E Tromboseunclassified